Apakah Pembelajaran Online Meningkatkan Preferensi Mahasiswa dalam Melakukan Kecurangan Akademik? Dimensi Fraud Pentagon - Kurniawati, Estetika Mutiaranisa; Jayanti, Risca Dwi; Chayati, Nur; Endiramurti, Saktiana Rizki (E-Jurnal Akuntansi, 2022)
The study aims to provide empirical evidence to analyze the factors that encourage students to take academic fraud actions when learning online during the Covid-19 pandemic. The data in this study are primary data collected through a survey technique using a questionnaire. The respondents obtained were as many as 273 undergraduate accounting students at a university in Central Java. The data analysis method to test the hypothesis used in this study is multiple linear regression using the SPSS 24 application. Based on the regression test, it was found that pressure, opportunity, rationalization, and ability variables have a significant effect on academic cheating behavior during online learning. On the other hand, the arrogance variable has no significant effect on cheating behavior in online learning. Keywords: Academic Fraud; Fraud Pentagon; Online Learning